Diversity of Demersal Fish Resources in Ambon Island Waters - Friesland Tuapetel; Delly DP Matrutty; Welem Waileruny (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2018)
The waters surrounding Ambon Island is a potential fishing gound for demersal fish resources, yet information regarding species diversity is still slightly understood. This research aimed to analyze the diversity of species and size of demersal fish around Ambon Island oceans. Data was collected based on experimental fishing using fish trap at two locations, in northern and southern waters of Ambon Island. The data were collected by experimental capture using fishing gear at two locations, namely northern waters (March-April 2015) and south of Ambon Island (July-October 2016). Methods of demersal resource diversity analysis are several ecological indexes i.e. Shannon-Wiener diversity index, Pielou uniformity index, and Simpson's dominance index. The result showed that 21 family and 57 species with details of 35 species in the northern waters and 32 species in the southern water. Species diversity based on Shannon-Wiener Index (H´) ranged between 1,61-3,10 while species evenness index (E) was around 0,83-0,95. The abundance of demersal fish was not dominated by any fish species, showed by the average Simpson index of dominant (D) around 0,05-0,26. Abstrak Perairan Pulau Ambon termasuk daerah penangkapan sumber daya ikan demersal yang potensial, namun informasi ke-anekaragamannya masih sangat sedikit. Penelitian ini bertujuan untuk menganalisis kekayaan jenis dan keanekara-gaman ikan demersal di perairan Pulau Ambon. Pengambilan data dilakukan dengan cara penangkapan eksperimental dengan menggunakan alat tangkap bubu pada dua lokasi yakni perairan utara (Maret-April 2015) dan perairan selatan Pulau Ambon (Juli-Oktober 2016). Metode analisis keanekaragaman sumber daya ikan demersal menggunakan bebe-rapa indeks ekologi yakni indeks keanekaragaman Shannon-Wiener, indeks keseragaman Pielou, dan indeks dominansi Simpson. Hasil penelitian menunjukkan bahwa di perairan Pulau Ambon teridentifikasi 21 famili dan 57 spesies de-ngan rincian 35 spesies di perairan utara dan 32 spesies di perairan selatan. Status keanekaragaman jenis indeks Shannon-Wiener (H´) berkisar 1,61-3,10 sedangkan indeks keseragaman jenis (E) sebesar 0,83-0,95. Kelimpahan ikan demersal tidak ada yang dominan, ditunjukkan oleh indeks dominan Simpson (D) sebesar 0,05-0,26.